1939
DOI: 10.1172/jci101059
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISM OF THE ARTERIAL HYPERTENSION INDUCED BY PAREDRINOL (α-N-DIMETHYL-p-HYDROXYPHENETHYLAMINE

Abstract: In arterial hypertension the cardiac output, the metabolic rate, and the usual blood chemical constituents are essentially normal. Experimental hypertension in man, however, is usually attended by alterations in some of these measurements. Epinephrine produces hypertension in normal subjects, but at the same time it usually increases the heart rate and cardiac output. It elevates the basal metabolism, the blood flow in the muscles, the blood sugar and the blood lactic acid, and also causes great vasoconstricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1940
1940
1948
1948

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…These findings are in agreement with those reported by Stead and Kunkel (7) in 2 subjects following the administration of a methyl derivative of paredrine. In 1 instance (Case 12) a decrease in cardiac output and slowing of circulation time due to the action of the vagal reflex were detected.…”
Section: Methodssupporting
confidence: 93%
“…These findings are in agreement with those reported by Stead and Kunkel (7) in 2 subjects following the administration of a methyl derivative of paredrine. In 1 instance (Case 12) a decrease in cardiac output and slowing of circulation time due to the action of the vagal reflex were detected.…”
Section: Methodssupporting
confidence: 93%
“…The effects in normal subjects of the intramuscular administration of paredrinol have been reported (5). The subjects experienced no symptoms except palpitation.…”
Section: Discussionmentioning
confidence: 94%
“…Such a substance should not cause increased oxygen consumption or widespread chemical changes in the body. From studies of normal subjects it was found that paredrinol 1 (a-N-dimethyl-p-hydroxyphenethylamine) fulfilled several of these requirements (5). Therefore its action was investigated in the collapse induced by sodium nitrite and in that accompanying postural hypotension and acute infectious disease.…”
mentioning
confidence: 99%
“…The above-described studies established the degree of change in the venous system after the administration of paredrine and to some extent also defined the mechanism of this change. In order to evaluate the importance of changes in the venous system on the genesis of the (2,3,6,12,13), while others regard back-pressure from the heart as the cause (10,11).…”
mentioning
confidence: 99%
“…It is most probable that venous constriction is one factor responsible for the rise in venous pressure caused by paredrine. This mechanism is not unique to paredrine, for the venous pressure increase produced by adrenalin in animals and men has been attributed to venous contraction (9,12,13), as has that produced by paredrinol (2,3,4,6). Measurements of the femoral venous pressure after the administration of paredrine show that the increases in pressure occur in these veins also.…”
mentioning
confidence: 99%